2022
DOI: 10.1186/s13054-022-04186-8
|View full text |Cite
|
Sign up to set email alerts
|

Oxygen targets and 6-month outcome after out of hospital cardiac arrest: a pre-planned sub-analysis of the targeted hypothermia versus targeted normothermia after Out-of-Hospital Cardiac Arrest (TTM2) trial

Abstract: Background Optimal oxygen targets in patients resuscitated after cardiac arrest are uncertain. The primary aim of this study was to describe the values of partial pressure of oxygen values (PaO2) and the episodes of hypoxemia and hyperoxemia occurring within the first 72 h of mechanical ventilation in out of hospital cardiac arrest (OHCA) patients. The secondary aim was to evaluate the association of PaO2 with patients’ outcome. Methods Preplanned … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

5
5

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 51 publications
(74 reference statements)
0
13
0
Order By: Relevance
“…Robba et al performed a secondary analysis of the TTM 2 trial, investigating the effects of hypo-and hyperoxemia within the first 72 h of admission on mortality and neurological status at 6 months. This multivariate Cox regression also showed a U-shaped distribution for PaO 2 with an increased risk for mortality below 69 mm Hg (hypoxemia) and above 195 mm Hg (hyperoxemia); however, it found no correlation for poor neurological outcomes [21]. PaO 2 was significantly lower in non-survivors for up to 32 h after ICU admission.…”
Section: Oxygenation/ventilationmentioning
confidence: 61%
“…Robba et al performed a secondary analysis of the TTM 2 trial, investigating the effects of hypo-and hyperoxemia within the first 72 h of admission on mortality and neurological status at 6 months. This multivariate Cox regression also showed a U-shaped distribution for PaO 2 with an increased risk for mortality below 69 mm Hg (hypoxemia) and above 195 mm Hg (hyperoxemia); however, it found no correlation for poor neurological outcomes [21]. PaO 2 was significantly lower in non-survivors for up to 32 h after ICU admission.…”
Section: Oxygenation/ventilationmentioning
confidence: 61%
“…The PaO 2 -cut point for worse outcome started at ≥ 40 kPa. In a recently published sub-analysis of the Target Temperature Management 2 (TTM2) trial, both hypoxemia and severe hyperoxemia were significantly associated with 6 month-mortality [ 43 ]. The best cut-off point associated with 6 month-mortality was 195 mmHg (26 kPa), which resembles the results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence consistently points to the association of hypoxemia with worse clinical outcomes in patients with ABI. In cardiac arrest patients, a sub-analysis of the TTM2 trial found that the best hypoxemia threshold for predicting 6-month mortality was PaO 2 <69 mmHg [59 ▪ ]. Hyperoxemia has also been associated with worse outcomes [60,61], putatively via free radical production and nitric oxygen scavenging [62].…”
Section: Ventilatory Targets In Brain Injurymentioning
confidence: 99%